2013
DOI: 10.1016/j.pain.2012.12.016
|View full text |Cite
|
Sign up to set email alerts
|

The influence of music and music therapy on pain-induced neuronal oscillations measured by magnetencephalography

Abstract: Modern forms of music therapy are clinically established for various therapeutic or rehabilitative goals, especially in the treatment of chronic pain. However, little is known about the neuronal mechanisms that underlie pain modulation by music. Therefore, we attempted to characterize the effects of music therapy on pain perception by comparing the effects of 2 different therapeutic concepts, referred to as receptive and entrainment methods, on cortical activity recorded by magnetencephalography in combination… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
41
5
8

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(58 citation statements)
references
References 30 publications
0
41
5
8
Order By: Relevance
“…This theory asserts that stimulation by non-noxious input is able to suppress pain. However, a recent study reported that music therapy modulates pain perception through at least two different mechanisms that involve changes in the activity of delta and gamma bands at different stages of pain processing [49]. These results provided novel insights into the neurological principals that underlie the achievement of pain relief following music therapy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This theory asserts that stimulation by non-noxious input is able to suppress pain. However, a recent study reported that music therapy modulates pain perception through at least two different mechanisms that involve changes in the activity of delta and gamma bands at different stages of pain processing [49]. These results provided novel insights into the neurological principals that underlie the achievement of pain relief following music therapy.…”
Section: Discussionmentioning
confidence: 99%
“…More studies are needed to reveal the roles of music intervention, especially music therapy, in severe pain control. However, based on the above-referenced study by Hauck et al [49], the combination of relaxation and distraction with music intervention may help patients cope with pain. Although individual studies have shown that submitting burn patients to music interventions provides some evidence of decreased pain intensity and anxiety, there have been no indications that any specific type of music offers more benefits.…”
Section: Discussionmentioning
confidence: 99%
“…Mitchell et al (2006) found that preferred music helped participants to tolerate pain longer than with music chosen by the experimenter. It is not yet known which are the specific mechanisms behind music-induced analgesia, however the evidence suggests that the intrinsic and extrinsic properties of the music should have an indirect influence on the effect via cognitive and emotional mechanisms (Roy et al, 2008, 2012; Bernatzky et al, 2011; Hauck et al, 2013). It is culturally and scientifically known that music is a powerful inducer of emotions and a modulator of mood (Baumgartner et al, 2006; Juslin and Västfjäll, 2008; Fritz et al, 2009; Bernatzky et al, 2011), and it is also known that emotions and mood can reduce pain (de Tommaso et al, 2008; Villemure and Bushnell, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Wie unmittelbar besonders die subjektiv relevanten musikalischen Stimuli auf die Schmerzverarbeitung von gesunden Probanden Einfluss nehmen, konnte in der neurophysiologischen Studie von Hauck et al (2013) unter Verwendung von MEG-Messungen nachgewiesen werden. Dass therapeutische Interventionen mit musikbezogenen Aktivitäten sogar neuroplastische Umstrukturierungen zur Folge haben können, zeigen eine EEG-Studie mit 32 Schlaganfallpatienten ) sowie eine spezifische MRT-Studie mit 6 Aphasiepatienten (Schlaug et al 2009).…”
Section: Neurowissenschaftliche Zugänge Zur Emotionalen Wirkung Von Munclassified